Makeup Remover Optimization: Unveiling the Power of Coffee Bean and Sunflower Oils in Cosmetics - Juha, Rama; Yakti, Reyyan; Sahin, Fatma Irem; Acarali, Nil (SOC COSMETIC CHEMISTS, 2024)
In this study, the effects of oils, specifically coffee bean oil and sunflower oil, were investigated in makeup cleansers which were used daily and had significant effects on the skin. The Box-Behnken Method in Design Expert was utilized to optimize the preparation of the makeup remover. For optimization, 29 experiments were formed with 4 parameters and 3 levels. Coffee bean and sunflower oils were mainly utilized, and experiments were conducted to assess the impact of varying concentrations of oils (2%, 4%, and 6%), different temperatures (25 degrees C, 30 degrees C, and 35 degrees C), and varying stirring times (5, 10, and 15 minutes) on the effectiveness of the product. The effectiveness of the cleansers were measured using a rubbing test. As a result, the predicted R 2 value of 0.9102 and the adjusted R 2 value of 0.9675 were close. Sample 16 with 4% coffee bean oil, 6% sunflower oil, 35 degrees C, and 10 minutes for stirring time was determined to be optimum. A comparison between all results in lipstick indicated a significant and positive reduction in the number of rubs required.
Keywords: EFFICACY; Chemistry; Dermatology